Agricultural services development project project feasibility study - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
In 1988, at the request of the IDB, IICA met with Bahamian agricultural sector authorities to prepare the Agricultural Services Development Project. This activity was divided into two phases; the first phase involved the identification of goals, strategies and the initiation of the project approach. The second phase consisted of a feasibility study, the development and conclusions of which are detailed in this document.